Linking functional traits and species preferences to species’ abundance and occupancy trends through time to identify habitat changes in coastal ecosystems - Pakeman, Robin J.; Hewison, Richard L.; Lewis, Rob J. (Perspectives in plant ecology, evolution and systematics, 2017)
•Species trends in occupancy and abundance were analysed for Scottish coastal habitats.•There was a general shift towards taller more exploitative species.•Changes have been faster and more negative in the least grazed and polluted sites.•Coastal heathlands were the habitat most affected by invading woody species. Coastal habitats are rich in biodiversity and provide highly valued ecosystem services. However, they are subject to many environmental drivers that can have severe impacts on these inherently fragile ecosystems. A resurvey approach was used to assess changes in species’ abundances and occupancy on sand dunes and machair in Scotland, UK to assess how this could impact on this set of habitats. These were assessed to see if increasers and decreasers shared common trait values, if trends were similar to other terrestrial habitats and if responses to environmental drivers were modulated by traits. In general, there has been a shift towards taller species with more exploitative growth forms and an increase in indicators of unfavourable habitat condition according to criteria for assessing sites designated for nature protection as part of the EU Natura 2000 network, particularly tall grasses characteristic of nutrient-rich conditions exemplified by Arrhenatherum elatius. Coastal heathlands have been particularly affected by the increase in species such as Betula spp. and Pteridium aquilinum which can dominate and exclude other heathland species. On average, increasing species were both more common nationally and increasing nationally, suggesting increasing homogenisation between sand dunes/machair and other terrestrial habitats. Changes have been faster and more negative in conservation terms in cooler, drier and more polluted sites (mainly on the east coast of Scotland) and also in sites which had seen reductions in grazing. Reinstating grazing could counteract some of the negative impacts of eutrophication, but this could prove problematic to integrate with recreational activities and the largely arable based farming systems adjacent to these sites.